KORELASI (MUNASABAH) AYAT DAN SURAH DALAM ALQURAN - M. Jabir (State Institute of Islamic Studies (IAIN) Palu, 2006)
The verses of the Qur’an were revealed little by little. Allah sometimes revealed only tens of verses, even one verse only. Apart from the number of verses revealed, the Prophet often conveied them to his revealation secretary that the verses had just been revealed was the continuation of the prior verses, or the beginning of the verses to reveal. It is from this point of view that the arrangement of the verses as found in Ottoman mushaf was not based on their choronological revealations, but on the harmony of their references and chapters. This article discusses one aspect of Qur’anic sciences, that is ‘Ilmu al-Munasabah or ‘Ilmu Tanasub al-Ayat wa al-Suwar the reference of the verses and cahpters. Kata Kunci: Munasabah, Ulumul Quran, Alquran, tafsir, surah, ayat